TMS coil design: Wire and winding considerations - Talebinejad, Mehran; Musallam, Sam (CMBES Proceedings, 2010)
Transcranial magnetic stimulation (TMS) is a method for stimulating human tissue especially neural tissue. An electric current in the stimulation coil produces a magnetic field, and a changing magnetic field induces a flow of electric current in nearby human tissue. TMS follows this fundamental principle and is well established in physiology, brain mapping and therapeutic applications. The simplest TMS coil is a circle, 5 to 15 cm in outer diameter that includes 5 to 50 turns. TMS coil windings are usually made of insulated copper wire. Rapid TMS with conventional coils quickly results in heat especially for prolonged high speed stimulation. This is due to high frequency current that tends to the outside of the wire bundle and increases the eddy currents inside the coil. This effect reduces the effective cross-sectional area of the coil, increasing the coil resistance, energy loss and heating. Coil cooling systems are generally required in such instances. Cooling system adds substantial weight and bulk. This has led to more elaborate and expensive designs using multi-stranded magnet wires. Previous research on TMS coil investigated coil arrays, and winding methods; these studies show interesting results based on numerical computations. However, the instrumentation challenge is in the details; it is not clear, what type of wire is exactly the best choice for TMS coil, and what type of winding results in a better structure for stimulation. In this paper, effects of wire and winding on TMS coil are studied. Round, square and rectangular magnet wires as well as braided and compacted Litz wires are compared. Horizontal- and vertical-spiral windings are compared. Results of a simulation study using finite element method are presented. Results show coil efficiency could be improved by the choice of wire and winding method. At last, a set of standards for wire, winding and inner diameter is presented.